Insights on the synthesis of asymmetric curcumin derivatives and their biological activities - Poh, Yen Khor; Mohd F. F., Mohd Aluwi; Kamal, Rullah; Kok, Wai Lam (Elsevier, 2019)
Curcumin is a small organic molecule with pleiotropic biological activities. However, its multiple structural-pharmacokinetic challenges prevent its development into a clinical drug. Various structural modifications have been made to improve its drug profile. In this review, we focus on the methods adopted in the synthesis of asymmetric curcumin derivatives and their biological activities and forecast the future of this exciting class of compounds in the field of medicine.